2018
DOI: 10.1038/s41380-018-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids metabolism, purine metabolism and inosine as potential independent diagnostic biomarkers for major depressive disorder in children and adolescents

Abstract: Major depressive disorder (MDD) in children and adolescents is a recurrent and disabling condition globally but its pathophysiology remains poorly elucidated and there are limited effective treatments available. We performed metabolic profiling of plasma samples based on ultra-high-performance liquid chromatography equipped with quadrupole time-offlight mass spectrometry to explore the potential biomarkers of depression in children and adolescents with MDD. We identified several perturbed pathways, including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 47 publications
5
96
1
Order By: Relevance
“…Data demonstrated lower levels of both inosine and guanosine, as well as higher levels of xanthine. A recent study carried out a metabolic profiling of plasma samples to explore the potential biomarkers of major depressive disorder in children and adolescents [103]. Authors identified several abnormal pathways, including purine metabolism, and highlighted that inosine might be a possible independent diagnostic biomarker of depression, achieving an area under the receiver operating characteristic curve of 0.999 and 0.866 in the identification of drug-naïve and drug-treated subjects with major depressive disorder, respectively.…”
Section: Purinergic Metabolism and Biomarkersmentioning
confidence: 99%
“…Data demonstrated lower levels of both inosine and guanosine, as well as higher levels of xanthine. A recent study carried out a metabolic profiling of plasma samples to explore the potential biomarkers of major depressive disorder in children and adolescents [103]. Authors identified several abnormal pathways, including purine metabolism, and highlighted that inosine might be a possible independent diagnostic biomarker of depression, achieving an area under the receiver operating characteristic curve of 0.999 and 0.866 in the identification of drug-naïve and drug-treated subjects with major depressive disorder, respectively.…”
Section: Purinergic Metabolism and Biomarkersmentioning
confidence: 99%
“…Approximately 100 μL of plasma was preprocessed for metabolomic analyses. The derivatives of the sample were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS), and the acquired data were processed as described in a previous study [28]. Metabolic profiling of mammary venous plasma was performed using an ultrahigh-performance liquid chromatography (UHPLC) instrument (1290 Infinity LC, Agilent Technologies) coupled to triple time-of-flight mass spectrometer (AB Sciex TripleTOF 5600) at Shanghai Applied Protein Technology Co., Ltd. Metabolic pathway analysis of the identified metabolites in MRDS vs. LRDS, HRDS vs. LRDS and HRDS vs. MRDS were determined using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database (http://www.genome.jp/kegg/).…”
Section: Metabolomic Analysismentioning
confidence: 99%
“…It is also an important pyridine bacterial secondary metabolite [20]. In addition, H8 is an intermediate in the metabolism of adenosine, which plays a role in energy transfer as ATP and serves as a strong pro-inflammatory danger signal targeting specifically gram-positive bacteria [21]; meanwhile, H8 is a potential independent diagnostic biomarker for major depressive disorder (MDD) in children and adolescents [22]. Although we found the above results interesting, further study to explore the direct relationship of these two metabolites to CSGS effects related to gut microbiota is necessary.…”
Section: Discussionmentioning
confidence: 99%